Plan de marketing para la comercialización de cinco hortalizas orgánicas de raíz en el cantón La Maná provincia de Cotopaxi, año 2014 - Zhunio Vera, Munir Galo (2015)
This research aims and a great purpose to develop a "MARKETING PLAN FOR THE MARKETING OF ORGANIC ROOT VEGETABLES FIVE IN THE MANNA CANTON 2014" Cotopaxi Province. It begins with zero marketing of organic vegetables caused by lack of knowledge on projects and low motivation among farmers originating in markets offering only traditional vegetables. Study techniques in the development process of the thesis the survey method with alternative barias, which took place at the people who came to the markets of central and open markets around the Canton La Mana was used in this work supports this marketing research where a score of shopping frequency, characteristics, needs was obtained. Earlier in the collection of information and the size of the sample population was obtained yielding a result of 378 respondents. THE Huertita the strategy to be implemented in organic root vegetables like carrots, beets, green onions, red onion and radish, is to publicize its benefits, its nutritional powers in various forms of preparation is proposed to all end consumers fresh and quality at a good price to everyone want to want to consume organic products. According to the proposal presented by the Huertita is being considered, marketing activities will be carried out with the initial 10 dealers throughout the year, with these data and the simulation run is considered that every trader should buy monthly $ 75, monthly $ 00 in total, would cover the projected investment this marketing plan, this gives us a total of $ 900.00 US dollars monthly, of this total is presumed that "Huertita" and traders would get a return of 10% this utility and the cost of the marketing plan is covered.